Pengenalan English Vocabulary Pada Anak Usia Dini Melalui English For Kids - Raden Agus Budiharto; S. Agus Santoso; Ratna Ani Lestari (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Given the English vocabulary instructional method used by teachers of PAUD Qurrotul Uyun Pamekasan is not groundbreaking and varied since they constantly teach the English vocabulary from the textbook, additionally they never employ a modern technology tool such as smartphone gadget. Despite the fact that they frequently bring the gadget when the teaching learning porcoses in the class is occurring. In view of that the learning atmosphere becomes unappealing, the pupils becomes passive and dependent learners. Hence the aim of community service activity is to give pupils of PAUD Qurrotul Uyun Pamekasan training regarding English vocabulary learning employing English For Kids application. Method used in this community service is training by utilizing steps with activity theoretically and practically. The results are to be able to enhance pupils’ leaning motivation, to be able to lessen pupils’ boredom while learning, as well as to be able to create pulpils become autonomous pupils.